Mapping of Ecosystems in Mount Bromo Using Remote Sensing Technology - Sukojo, Bangun Muljo (UI Scholars Hub, 2003)
Mapping of Ecosystems in Mount Bromo Using Remote Sensing Technology. Covered land analyses of Landsat image have been done to get ecosystem types and map in Mount Bromo region using remote sensing technology. There are nine types of ecosystems in Mount Bromo region, i.e. primary forest, secondary forest, lake, crater, sands, uncovered land, underbrush, dry-field and residence. Distribution of rock analysis has also been done by comparing the manual image interpretation with geological map. The results were coorelated with the digital image interpretation to find rock distribution map which can be useful to get the information about water reservation potencial in Mount Bromo region. The coorelation results together with slope, covered vegetation and rain falls can give description about absolute water reservation and buffer zone map in Mount Bromo region.